2019
DOI: 10.1080/21691401.2019.1626863
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid-modified selenium nanoparticles for enhancing the therapeutic efficacy of paclitaxel in lung cancer therapy

Abstract: Targeted delivery of chemotherapeutics by functionalized nanoparticles exhibits a wonderful prospect for cancer treatment. In this paper, selenium nanoparticles (SeNPs) was linked with hyaluronic acid (HA) to prepare tumor-targeted delivery vehicle HA-SeNPs, and HA-SeNPs was loaded with paclitaxel (PTX) to fabricate functionalized selenium nanoparticles HA-Se@PTX. HA-Se@PTX showed greater uptake in A549 cells in comparison with that in HUVEC, verifying HA-mediated specific uptake of HA-Se@PTX. HA-Se@PTX was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…During the formation of Selenium element, the presence of some templates, also recognized as stabilizers, would lead these Selenium element to form nano-sized particles in aqueous solutions. A lot of chemicals can be used as templates for Se NPs preparation, such as chitosan (Bai et al, 2017), folate (Pi et al, 2013), hyaluronic acid (Zou et al, 2019),polyethylenimine (PEI) and ferulic acid (Cui et al, 2018b). In terms of the low cost, convenient procedure and controllable size, these template methods thus offer novel design of Se NPs with high efficacy.…”
Section: Selenium Nanoparticles Prepared By Template Methodsmentioning
confidence: 99%
“…During the formation of Selenium element, the presence of some templates, also recognized as stabilizers, would lead these Selenium element to form nano-sized particles in aqueous solutions. A lot of chemicals can be used as templates for Se NPs preparation, such as chitosan (Bai et al, 2017), folate (Pi et al, 2013), hyaluronic acid (Zou et al, 2019),polyethylenimine (PEI) and ferulic acid (Cui et al, 2018b). In terms of the low cost, convenient procedure and controllable size, these template methods thus offer novel design of Se NPs with high efficacy.…”
Section: Selenium Nanoparticles Prepared By Template Methodsmentioning
confidence: 99%
“…The HA-SeNPs efficiently controlled the immune-regulating properties and decreased the tumor mass. [171][172][173][174] Moreover, a study reported that magnesium oxide nanoparticles combined with human serum albumin exhibited better plasma distribution and mediate apoptosis by ROS induced in the cell lines of cancer. 175 Furthermore, a similar study on magnesium oxide (MgO) nanostructures showed excellent photocatalytic, antibacterial, and anticancer performance.…”
Section: Therapeuticsmentioning
confidence: 99%
“…Anti-MDR drugs (such as apatinib) co-delivered together with PTX have shown a favorable efficacy enhancement (Zhang et al, 2020). It was found that HA-functionalized vehicles with a PTX payload notably suppressed tumor invasion, migration, and proliferation, including micelles (HA-CA), selenium NPs (HA-Se@PTX), and mesoporous hollow alumina NPs (PAC-HMHA) (Thomas et al, 2015;Gao et al, 2019;Zou et al, 2019;. Previous studies have shown that HA-coated nanostructured lipids delivering PTX remarkably prolonged blood retention and tumor accumulation compared with Taxol (Yang et al, 2013).…”
Section: Hyaluronic Acid (Ha) and Chondroitin Sulfate (Cs)mentioning
confidence: 99%